Children’s Perceptions of Poverty - Hakovirta Mia; Kallio Johanna (Springer Netherlands, 2022)
This article explores children’s perceptions of poverty and its causes; we want to know how children perceive poverty and what they think causes it. The study applied a qualitative approach, and the research data consisted of 30 semi-structured interviews with children aged 10–15. Respondents were not specifically recruited by any socioeconomic criteria and according to FAS children represent middle affluence group. The data was collected in the school located in one of the largest urban regions in Finland, in city in the outer urban area. The data were processed using content analysis and the major themes emerging from the data as a whole are the focus of this article. Children saw poverty as a relative absence of non-essential goods and items due to the scarcity of financial resources. It was not a question of poorer children lacking daily necessities, such as a home, clothes, equipment for leisure activities, or a mobile phone, but rather of poorer children having models that were outdated, or second-hand or broken goods. Poverty was seen as a phenomenon that almost by necessity shapes and influences people’s ways of thinking and actions. Poverty was also associated with humility, and poor children were considered to carry a social stigma. We condensed the children’s perceptions regarding the causes of poverty into six themes: individual blame, individual action, societal blame, societal situation, individual fate, and social fate. Some children emphasised the role of individual interpretations and independent choices; for others, poverty was ultimately explained by structural factors. Overall, however, the main accent was on structural explanations. On the other hand, these two sets of explanations also coexisted concurrently in children’s experiences, so that poverty was seen at once as both an individual and a societal phenomenon.